Analisis Pengaruh Rekruitmen Meliputi Seleksi, Pelatihan dan Penempatan Kerja Terhadap Kinerja Karyawan(Pada PT. Liebra Permana Wonogiri) - Bawono, Adhi; , Ir. Irmawati, S.E., M.Si (2017)
The purpose of this study to determine whether the recruitment process that includes the selection, training and job placement have an influence on employee performance and to determine the combination of selection, training and job placement have an influence on employee performance. The population used in this study were employees of PT. Permana Liebra Wonogiri totaling 1680 employees. This study used a sample of 95 respondents, method of data collection using the questionnaire with simple random technique samplingsebagai taken. Testing the hypothesis in this study using a statistical model analysis consisting of validity, reliability, classic assumption test, multiple linear regression, F test, t test, and the coefficient of determination (R2). The results showed a correlation between the independent variables are the selection, training and job placement on the dependent variable is the performance of employees. Value hypothesis test (t-test) found that the selection of variables have an influence on the performance of employees, training variables have an influence on the performance of employees, and job placement variables have an influence on employee performance. F test showed that the selection, training and job placement together have an influence on employee performance. Coefficient determination of the employee's performance is affected by the variable selection, training and job placement, and the model has escaped from the classical assumptions.